Front Metter SOCA January Vol 15, No 1, 2021 - January Vol 15, No 1, Front Metter SOCA (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol 15 No 1 (2021): Vol.15, No.1, 2021, 2021)
Front Metter SOCA January Vol 15, No 1, 2021